Shapes Displayed with Durations in the Microsecond Range Do Not Obey Bloch's Law of Temporal Summation. (September 2013) - Greene, Ernest; Ogden, R. Todd
Shape patterns were displayed with simultaneous brief flashes from a light-emitting diode array. Flash durations in the microsecond range and luminous intensities were adjusted to vary the degree of successful shape recognition. Four experiments were conducted to test whether Bloch's law would apply in this task. Bloch's law holds that for very brief flashes the perceptual threshold is determined by the total number of photons being delivered, i.e., there is reciprocity of intensity and duration. The present results did not find that effectiveness of flashes was based on the total quantity of photons, as predicted by Bloch's law. Additionally, the evidence points to a visual mechanism that has ultra-high temporal precision that either registers the rate of photon flux or the duration of flashes.